Value creation through collaborative supply chain: Holistic performance enhancement road map - Holimchayachotikul,P. (Taylor and Francis Ltd., 2015)
This paper proposes an integrated novel framework between B2B-SCM using data mining techniques such as K-Means based on particle swarm intelligence (particle swarm optimisation) and association rule. It constructs relationship rules of holistic performance enhancement road map. The data-set of relationships between enterprise and its direct customers of the case study organisations in France was used for demonstration. The experiment results show how domain managers powerfully utilise the graphical analysis results to provide the holistic performance improvement and weakness resolution relationship rules. In the long run, organisations are able to use this framework to design and adjust their units to conform the exact customer needs. This paper introduces and explains a new idea of measuring value added along the supply chain from a collaborative perspective. The extended model is adapted from our previous model and from balanced scorecard model. It provides a tool to measure tangible and intangible value between partners. © 2013 Taylor and Francis.